2019
DOI: 10.1136/bmjopen-2019-029319
|View full text |Cite
|
Sign up to set email alerts
|

Examining the information needed for acceptance of deintensified screening programmes: qualitative focus groups about cervical screening in Australia

Abstract: ObjectivesGiven the changing understanding of overdiagnosis of screen detected cancers and advances in technology to detect and prevent cancer, updating and scaling back cancer screening programmes is becoming increasingly necessary. The National Cervical Screening Programme (NCSP) in Australia was recently deintensified, with the changes implemented in December 2017. This study examines women’s understanding and acceptance of the renewed screening protocol and how such changes can be communicated more effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…This is important as our previous research showed that communicating to women about the change in test can then help provide reassurance and understanding to women about some of the other changes to the programme. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This is important as our previous research showed that communicating to women about the change in test can then help provide reassurance and understanding to women about some of the other changes to the programme. 21 …”
Section: Discussionmentioning
confidence: 99%
“…As previously described ( Dodd et al, 2019 ), six focus groups were conducted with women aged 18–74 across three locations in Sydney, Australia. Each group consisted of 5–10 women, divided by eligible age ranges (18–30, 31–50 and 51–74 years) for both the previous (1991–2017, age 18–69) and current (2017-present, age 25–74 years) NCSP.…”
Section: Methodsmentioning
confidence: 99%
“…An initial announcement of the changes was made by the Australian government in April 2014, but no mass awareness campaign informed the public prior to its implementation. A petition against the changes in early 2017, started by an Australian woman who was concerned and worried after being informed about the changes by her GP, gathered over 70,000 signatures, suggesting that there was a considerable amount of resistance ( Obermair et al, 2018 ), which appeared to arise due to a lack of knowledge and understanding about the reasons behind the changes ( Dodd et al, 2019 ). The NCSP used to recommend screening women aged 18–69 every two years with cytology-based screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus group findings supported the need for women to have clear and coherent information prior to implementing significant programme changes. They identified what information women sought, as well as what information is helpful in explaining the changes to the programme 8. Together these studies suggest that many Australian women may have suboptimal understanding of the renewed NCSP.…”
Section: Introductionmentioning
confidence: 99%